2020
DOI: 10.20884/1.jm.2020.15.2.533
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antioxidant Activity of Brotowali (Tinospora crispa L. Mier) Stem

Abstract: Free radical in the body could cause degenerative diseases such as diabetes mellitus and hyperlipidemia, which could be prevented by the supplementation of antioxidant whether it is synthetic or natural. Flavanoids is a phenolic compound, was extracted from natural sources is known for its antioxidative potential. This research aimed to investigate the active compounds in brotowali (Tinospora crispa) stem to find new antioxidative potential using its ability to bind 2, 2’-diphenyl-1-picrylhydrazyl (DPPH). Brot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
0
8
0
5
Order By: Relevance
“…While water solvent showed a high yield up to 31.22 % (W/W) 9 and 57.9 % (W/W). 14 The total flavonoid (TFC) and phenolic (TPC) content were determined and expressed in % (W/W) unit. The data indicated that both flavonoid and phenol antioxidative properties including the total flavonoid content, the phenolic content, and antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…While water solvent showed a high yield up to 31.22 % (W/W) 9 and 57.9 % (W/W). 14 The total flavonoid (TFC) and phenolic (TPC) content were determined and expressed in % (W/W) unit. The data indicated that both flavonoid and phenol antioxidative properties including the total flavonoid content, the phenolic content, and antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…In another study using a DPPH assay, the ethanol extract, its water fraction and selected subfractions, showed IC 50 values of 49.92 μg/mL, 38.25 μg/mL, 36.12 μg/mL, and 16.18 μg/mL, respectively. It was postulated that acid hydrolysis of the subfractions improved their antioxidant potential (Warsinah et al 2020 ). Several other studies measuring the total phenolic content, total flavonoid content, DPPH free radical scavenging activity and Ferric Reducing Antioxidant Power of T. crispa all confirned the antioxidant potential of the plant (Zulkefli et al 2013 ; Abood et al 2014 ; Nguyen et al 2020 ; Mahalle and Gupta 2021 ).…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…Tanaman tropis telah diteliti kemampuannya untuk mengatasi kondisi hiperglikemia, diantaranya mimba (Azadirachta indica), cempedak (Artocarpus champeden), manggis (Garcinia mangostana), rambutan (Nephelium lappaceum), soga Peltophorum pterocarpum), jambu air (Syzygium aqueum), jamblang (Syzygium cumini), dan anggur (Vitis vinifera) (Manaharan et al, 2012). Selain itu, beberapa tanaman yang telah digunakan sebagai agen antihiperglikemia yaitu brotowali (Tinospora crispa) (Pramudya et al, 2020;Purnamasari, 2021;Warsinah et al, 2020), sambiloto (Andrographis paniculata) (Syukri et al, 2015;Nugroho et al, 2016), kayu manis (Cinnamomum burmannii) (Damayanti, 2014;Mila, 2016;Anna & Firdus, 2017;Cheng et al, 2012), dan meniran (Phyllantus niruri) (Iswahyudi et al, 2018).…”
Section: Pendahuluanunclassified
“…Dosis ekstrak tanaman unggul Indonesia yang diberikan melalui rute oral pada tikus wistar jantan (Ahmad et al, 2013). (Prahanarendra, 2015;Warsinah et al, 2020).…”
Section: Perlakuan Hewan Ujiunclassified